Pseudoautosomal regions at the tip of the short and long arms of the human sex chromosomes - Rappold, Gudrun (Advances in genome biology, 1996)
This chapter discusses the pseudoautosomal regions present at the tip of the short and long arms of human sex chromosomes. Of all human chromosomes, the sex chromosomes, X and Y, have always been the focus of intensive gene mapping efforts. For the X chromosome, this is because of the unique inheritance of x-linked genes, which has allowed the early identification of numerous X-linked recessive traits of medical importance. For the Y chromosome, it is because of its small size and its primary role in male development. It seems likely, therefore, that the sex chromosomes is one of the first chromosomes to be saturated with markers, genes, and sequenced regions. This information is being generated through physical and genetic maps, YAC and cosmid contigs, and eventually through the sequence of it's approximately 160 (X) and 60 (Y) million base pairs of DNA. The chapter focuses on the structure and functions of this region and discusses some of its unique and fascinating properties. The common past of the human sex chromosomes is emphasized by the observation that different X-Y homologous regions with varying degrees of conservation have been found on both the long and the short arm of the human X and Y.
Gesehen am 24.03.2021